2019
DOI: 10.1002/ange.201900901
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flavin Mononucleotide as a Cell‐Active Artificial N6‐Methyladenosine RNA Demethylase

Abstract: N 6 -Methyladenosine (m 6 A) represents ac ommon and highly dynamic modification in eukaryotic RNAt hat affects various cellular pathways. Natural dioxygenases such as FTOa nd ALKBH5 are enzymes that demethylate m 6 A residues in mRNA. Herein, the first identification of as mallmolecule modulator that functions as an artificial m 6 A demethylase is reported. Flavin mononucleotide (FMN), the metabolite produced by riboflavin kinase,mediates substantial photochemical demethylation of m 6 Ar esidues of RNAinl ive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…Current methods of manipulating RNA methylation are primarily based on modulating the expression of RNA methyltransferases (Mettl3/Mettl14/WTAP complex) or demethylase (FTO and/or ALKBH5) via bioengineering methods, which cause broad epigenetic changes and activation of endogenous retroviruses 9,[11][12][13][14] . Recently, flavin mononucleotide was identified as a cell active artificial m 6 A RNA demethylase, which provided a potential and powerful small molecule for RNA demethylation 15 . However, as these methods and reagents demethylate transcriptome globally, it is difficult to study the effect of specific RNA methylation events, and there is the risk of side effects in therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…Current methods of manipulating RNA methylation are primarily based on modulating the expression of RNA methyltransferases (Mettl3/Mettl14/WTAP complex) or demethylase (FTO and/or ALKBH5) via bioengineering methods, which cause broad epigenetic changes and activation of endogenous retroviruses 9,[11][12][13][14] . Recently, flavin mononucleotide was identified as a cell active artificial m 6 A RNA demethylase, which provided a potential and powerful small molecule for RNA demethylation 15 . However, as these methods and reagents demethylate transcriptome globally, it is difficult to study the effect of specific RNA methylation events, and there is the risk of side effects in therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, this method, along with other labelling reactions, can not distinguish f 5 C from another formyl containing f 5 U. In our continuous effort to explore opto-bioorthogonal chemistry of RNA modifications, [33][34][35][36][37][38] we envisioned that a 4,5-type cyclization with both N 4 -amino and C5formyl functionalities would be an ideal solution to this. We firstly explored a bunch of nucleophiles that could selectively react with the carbonyl substituent (Table S1).…”
Section: Results and Disscusionsmentioning
confidence: 99%
“…MALDI-TOF analysis (Figure S18) and enzymatic cleavages (Figure 2F) also confirmed that the chemical recognition and functionalization with Wittig reagent 1 showed no sequence or conformation preference but a high selectivity for f 5 C modification, which is consistent with our previously developed chemical modulation of RNA epigenetics with small organic molecules. 37,38,54 with Wittig reagent 1 before (hν ˗ ) and after light irradiation (hν + ). HPLC chromatograms with a wavelength of 260 nm and 350 nm were recorded respectively.…”
Section: Results and Disscusionsmentioning
confidence: 99%
“…So far, only 3‐deazaadenosine has been proven to inhibit METTL3, but it has a broad‐spectrum efficacy and inhibits the activity of all m 6 A “readers” 140 . Furthermore, chemical oxidation eliminates the m 6 A modification of mRNA 141,142 . Although several m 6 A demethylase agents have been reported in the literature, their specificity or efficacy cannot achieve the goal of precise and suboptimal treatment.…”
Section: M6a and Related Inhibitorsmentioning
confidence: 99%